Kotlin Programming Cookbook - Rashi Karanpuria; Aanand Shekhar Roy (Packt Publishing, 2018)
Dive into "Kotlin Programming Cookbook", your comprehensive recipe book for mastering Kotlin. With practical examples and clear explanations, you'll seamlessly navigate Kotlin's features and learn how to tackle real-world programming challenges. From Android development to functional programming, this book equips you to build robust applications using Kotlin, Spring Boot, and Android.What this Book will help me doGain a solid understanding of Kotlin basics and advanced object-oriented concepts.Master Android programming using Kotlin, SQLite databases, and network communication.Harness Kotlin's unique features like Lambdas and Delegates for functional programming.Develop and secure web services and RESTful APIs with Kotlin and Spring Boot.Learn effective testing strategies for Kotlin applications, from unit to acceptance tests.Author(s)Aanand Shekhar Roy and Rashi Karanpuria are experienced software developers and educators. Their expertise spans developing scalable applications and teaching modern technologies like Kotlin and Android development. They blend deep technical know-how with practical, real-world insight to create a resource-rich learning experience for aspiring Kotlin developers.Who is it for?This book is tailored for developers who are eager to strengthen their programming skills with Kotlin. It's ideal for beginners familiar with Java who want to expand their expertise in Android or web app development. Whether you're a mobile developer or a backend programmer, you'll find practical recipes that address common challenges. If you're seeking actionable guidance to elevate your Kotlin knowledge, this book is for you.